Literature, Idea and the Feminist Consciousness in Charlotte Perkin Gilman’s “The Yellow Wall-Paper” - Okwudiri Anasiudu (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
Literature reproduces social realities. These realities are furnished through ideas and form in the service of a society and every of its moments and events in history. Drawing from the foregoing proposition, this study explores the connection between literature, idea, and the feminist consciousness in Charlotte Perkin Gilman’s “The Yellow Wall-Paper” in order to demonstrate Gilman’s foregrounding of the challenge of a married woman. This study notes that Gilman’s portrayal re-echoes the challenges of contemporary women against the exertions of patriarchy, and the denial of the female voice and agency in marital space. Gilman underscores her theme through specific narrative strategies such as the creation of a cognitively active and questioning female character; who is prevented from exercising her artistic abilities and whose agency is stifled as a house wife without a name in contrast to her husband Dr. John. Another strategy is through the use of symbols such as the yellow wall paper to allegorize the female condition in marital sphere in the similitude of a prison and a caged existence. Importantly, while this paper locates the society as an important source of inspiration for the feminist idea manifest in “The Yellow Wall-Paper”, this paper submits that Gilman makes a demand for social change, and her short story constitutes a type of resistance to the narrative framing of women in domestic sphere by men, institution, authorities and orthodoxies as marginal and subalterns.